2019
DOI: 10.3856/vol47-issue3-fulltext-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stocking density on production and water quality of a photo heterotrophic intensive system of white shrimp (Penaeus vannamei) in circular lined grow out ponds, with minimal water replacement

Abstract: This work aimed to determine the optimum stocking density of Penaeus vannamei, cultured in a photo-heterotrophic intensive circular system inlined grow-out ponds with minimal water replacement. Five intensive density levels (100, 300, 500, 700 and 900 ind m-3) were considered. The water quality measured for the 98 days grow-out period was within the adequate range for P. vannamei. TAN, nitrate and total phosphorus water quality were significantly higher (P < 0.05) at the higher density. Growth rates and surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
2
10
0
1
Order By: Relevance
“…Gompertz‐D2 and Potential‐D models suggest a final shrimp size of 11.90–9.56 g and 8.68–7.72 g at initial culture densities from 90 to 180 shrimp/m 2 and 230 to 330 shrimp/m 2 respectively. These results are in agreement with Arambul‐Muñoz et al (2019), Gao et al (2017), Yu et al (2009) and Williams et al (1996). Similar observations have been reported for studies of L. vannamei and P. setiferus (Araneda et al, 2008; Williams et al, 1996) Consistent results have also observed similar patterns measuring different independent factors such as salinity and temperature (Appelbaum et al, 2002; Davis & Arnold, 1998; Roy et al, 2020; Samocha et al, 2004; Van Wyk et al, 1999; Williams et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gompertz‐D2 and Potential‐D models suggest a final shrimp size of 11.90–9.56 g and 8.68–7.72 g at initial culture densities from 90 to 180 shrimp/m 2 and 230 to 330 shrimp/m 2 respectively. These results are in agreement with Arambul‐Muñoz et al (2019), Gao et al (2017), Yu et al (2009) and Williams et al (1996). Similar observations have been reported for studies of L. vannamei and P. setiferus (Araneda et al, 2008; Williams et al, 1996) Consistent results have also observed similar patterns measuring different independent factors such as salinity and temperature (Appelbaum et al, 2002; Davis & Arnold, 1998; Roy et al, 2020; Samocha et al, 2004; Van Wyk et al, 1999; Williams et al, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…This observation confirms that increased shrimp densities in an intense aquaculture system lead to a reduction in biomass due to low survival and growth associated to the overcrowding stress (Suwoyo & Hendrajat, 2021; Yu et al, 2009) (Figure 2). Arambul‐Muñoz et al (2019) suggest a production with lower density can be more profitable, given that production time would increase in higher population densities, along with operational costs; yet economic analysis was not included in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that growth performance was declined by increasing the density of shrimp. These results were similar to those mentioned by several authors, who found that growth in L. vannamei and other penaeid species is stocking density-dependent (Moss & Moss, 2004;Yu et al, 2009;Arambul-Muñoz et al, 2019). The growth performance of shrimp in this study was lower than that recorded by other authors, who found that, at stocking densities ranging of 17 -45 shrimp/m 2 , and 40 -80 shrimp/m 2 , L. vannamei juvenile can grow between 20.70 to 25.25 g/shrimp, and 12.4 and 16.5 g/shrimp, respectively (Sookying et al, 2011;Nguyen et al, 2013).…”
Section: Shrimp Growth Performance and Feed Utilizationsupporting
confidence: 92%
“…Yu et al (2009) reported that increasing stocking densities reduced the growth performance and survival rate of cultured shrimp and water quality deterioration. Similarly, Arnold et al (2009) and Arambul-Muñoz et al (2019) found that density-dependent growth and survival in intensive shrimp culture could be mainly due to a combination of factors, including a decrease in the availability of natural food sources and space, an increase in cannibalism, decrease in water quality and accumulation of undesirable sediments.…”
Section: Introductionmentioning
confidence: 98%
“…En el cultivo intensivo de camarones, el crecimiento y la supervivencia dependientes de la densidad es una respuesta típica debida principalmente a una combinación de factores, entre los que se incluyen: la reducción de la disponibilidad de fuentes de alimento natural y del espacio, el aumento del canibalismo, la disminución de la calidad del agua y la acumulación de sedimentos indeseables (Arnold et al, 2006). Arambul-Muñoz et al, (2019) mencionan que el nitrógeno amoniacal total (TAN), el nitrato y el fósforo total de la calidad del agua, fueron significativamente más altos en la densidad más alta, además observaron que las tasas de crecimiento y la supervivencia disminuyeron a medida que la densidad aumentó después de 300 org m -3 de un sistema intensivo de camarón blanco (Penaeus vannamei) fotoheterotrófico. Krummenauer et al (2011) observaron en un cultivo superintensivo de Penaeus vannamei en un sistema de tecnología Biofloc (BFT) que, la densidad de siembra era probablemente la principal influencia en la supervivencia del camarón, verificando junto con otros estudios que la productividad de P. vannamei está limitada por un crecimiento reducido a medida que aumenta la densidad de siembra (Moss y Moss, 2004;Coman et al, 2004).…”
Section: Discussionunclassified